2006
DOI: 10.1002/chin.200627146
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Chain 3‐Acyl‐4‐hydroxycoumarins: Structure and Antibacterial Activity.

Abstract: A number of new 3-acyl-4-hydroxycoumarins endowed with marked antibacterial activity is synthesized (yields not given) and structure-activity relationships are discussed. -(CRAVOTTO*, G.; TAGLIAPIETRA, S.; CAPPELLO, R.; PALMISANO, G.; CURINI, M.; BOCCALINI, M.; Arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Hydroxycoumarins react remarkably quickly with several acyl chlorides to give acyl derivatives of coumarin [20][21][22][23][24][25][26][27][28][29][30][31][32]. Previous work has shown that phenols, particularly hydroxycoumarins and some similar compounds such as homophthalic anhydrides, are suitable for acylation reactions with different results.…”
Section: Synthesis Of 3-coumarinyl Carboxylatesmentioning
confidence: 99%
“…Hydroxycoumarins react remarkably quickly with several acyl chlorides to give acyl derivatives of coumarin [20][21][22][23][24][25][26][27][28][29][30][31][32]. Previous work has shown that phenols, particularly hydroxycoumarins and some similar compounds such as homophthalic anhydrides, are suitable for acylation reactions with different results.…”
Section: Synthesis Of 3-coumarinyl Carboxylatesmentioning
confidence: 99%